2015
DOI: 10.1109/tsp.2015.2451107
|View full text |Cite
|
Sign up to set email alerts
|

Fast Computation of Sliding Discrete Tchebichef Moments and Its Application in Duplicated Regions Detection

Abstract: International audienceComputational load remains a major concern when processing signals by means of sliding transforms. In this paper, we present an efficient algorithm for the fast computation of one-dimensional and two-dimensional sliding discrete Tchebichef moments. To do so, we first establish the relationships that exist between the Tchebichef moments of two neighboring windows taking advantage of Tchebichef polynomials’ properties. We then propose an original way to fast compute the moments of one windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In fact, the proposed method never exceeds 0.3 s in the testing as the Tchebychef Z-transform continues to rise. Table 4 presents different results from existing methods [33] showing the execution time of the DTMs calculation process up to the fifth order. Results are expressed in seconds.…”
Section: Test and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the proposed method never exceeds 0.3 s in the testing as the Tchebychef Z-transform continues to rise. Table 4 presents different results from existing methods [33] showing the execution time of the DTMs calculation process up to the fifth order. Results are expressed in seconds.…”
Section: Test and Resultsmentioning
confidence: 99%
“…On the other hand, if NB increases, more blocks are generated; the accuracy of moment's calculation is improved while time execution increases. The complexity proposed in [33] depends only on the moment's order which is good since the moment's order is generally a small number. However, the moment's order is put to the third power when calculating the number of additions and multiplications.…”
Section: Test and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the principle analysis of the three image resizing methods, we found that the correlation between adjacent pixels can be destroyed in the process of image resizing. Tchebichef moments have been extensively applied in field of image/vedio such as information security [18], pattern recognition [19] and image quality assessment [20], and so on. Inspired by this, it can be found from experiments that LTM can effectively reflect the correlation changes between adjacent pixels.…”
Section: Discussionmentioning
confidence: 99%
“…The most promising path is to find and compress redundant operations in the for-loop like processing of image patches. In this regard, useful properties of basis functions (such as shift properties in [74,75]) and special data structures (such as complex-valued integral images in [76]) have been explored to improve efficiency.…”
Section: B Fast Calculationmentioning
confidence: 99%